Cortical laminar necrosis related to prolonged focal status epilepticus. Issue 1 (16th December 2005) - Donaire, A; Carreno, M; Gómez, B; Fossas, P; Bargalló, N; Agudo, R; Falip, M; Setoaín, X; Boget, T; Raspall, T; Obach, V; Rumiá, J
Abstract : Cortical laminar necrosis (CLN) is radiologically defined as high intensity cortical lesions on T1 weighted MRI images following a gyral distribution. Histopathologically, CLN is characterised by pannecrosis of the cortex involving neurones, glial cells, and blood vessels. It has been reported to be associated with hypoxia, metabolic disturbances, drugs, and infections. We present two patients who developed CLN and permanent neurological deficits after prolonged and repeated focal status epilepticus. The possible mechanisms leading to CLN in these patients are discussed, together with the implications of prompt and aggressive treatment in similar cases.